"It's Not Just the Right Thing . . . It's a Survival Tactic": Disentangling Leaders' Motivations and Worries on Social Care. (October 2022) - Fraze, Taressa K.; Beidler, Laura B.; Savitz, Lucy A.
Health care organizations face growing pressure to improve their patients' social conditions, such as housing, food, and economic insecurity. Little is known about the motivations and concerns of health care organizations when implementing activities aimed at improving patients' social conditions. We used semi-structured interviews with 29 health care organizations to explore their motivations and tensions around social care. Administrators described an interwoven set of motivations for delivering social care: (a) doing the right thing for their patients, (b) improving health outcomes, and (c) making the business case. Administrators expressed tensions around the optimal role for health care in social care including uncertainty around (a) who should be responsible, (b) whether health care has the needed capacity/skills, and (c) sustainability of social care activities. Health care administrators could use guidance and support from policy makers on how to effectively prioritize social care activities, partner with other sectors, and build the needed workforce.